Pathogens and extracellular vesicles: New paths and challenges to understanding and treating diseases. Editorial opinion. (November 2021) - Ramirez, Marcel I.; Marcilla, Antonio
Highlights: EVs participate in cellular communicattion in both intra and interspecific levels (including mammalian host cells). EVs provide new targets for controlling infectious diseases. The exponencial increase in publicattions on EVs should let to get enoough funding to continue with basic and applied studies. Abstract: Extracellular vesicles (EVs) have been described in all eukaryotic and prokaryotic cells as released membranous structures loaded with biomolecules including nucleic acids, glycoconjugates, lipids and proteins. Two main groups of vesicles with different biogenesis and size are considered to be the most predominant, Exosomes (30–100 nm) originating from multivesicular bodies, and microvesículas (100–1000 nm) originating from plasma membrane. EVs participate in cellular communication between different organisms and can alter neighbour cells, participating in physiological and pathophysiological processes. In this issue, eleven reviews summarize the current knowledge in the characterization of EVs participating in the pathogenic-host interaction including protozoa, helminths, bacteria, fungi and viruses (Montaño et al., 2021; Palacios et al., 2021; Rossi et al., 2021; Sabatke et al., 2021; Cucher et al., 2021; Gilmore W et al., 2021; Sánchez-López et al., 2021; Dong et al., 2021; Drurey C and Mayzels R.M., 2021; Macedo-Da Silva J et al., 2021; Piffer, A. C et al., 2021).